Feminist Collections, v.13, no.4 (summer 1992) - (:unkn) unknown (My University, 1992)
Subtitle: A Quarterly of Women's Studies Resources. 40p.
FROM THE EDITORS. BOOK REVIEWS: THE PERSPECTIVES OF FOUR NATIVE AMERICAN WOMEN WRITERS, by Chris Jendrisak. [Reviews of] From the River's Edge, by Elizabeth Cook-Lynn; Mean Spirit, by Linda Hogan; Almanac of the Dead, by Leslie Marmon Silko; and Grandmothers of the Light: A Medicine Woman's Sourcebook, by Paula Gunn Allen. ACROBATS ON THE TIGHTROPE BETWEEN PHILOSOPHY AND FEMINISM: NOMADIC FEMALE FEMINISTS AND/OR FEISTY FEMINISTS? by Sharon Scherwitz. [Reviews of] Patterns of Dissonance: A Study of Women in Contemporary Philosophy, by Rosi Braidotti; and Feminist Ethics, ed. by Claudia Card. SOUTHERN WOMEN WRITERS AND THE LITERARY CANON, by Michele Alperin.[Reviews of] Homeplaces: Stories of the South by Women Writers, ed. by Mary Ellis Gibson; Female Pastoral: Women Writers Re-Visioning the American South, by Elizabeth Jane Harrison; Southern Women Writers: The New Generation, ed. by Tonnette Bond Inge; and Friendship and Sympathy: Communities of Southern Women Writers, ed. by Rosemary M. Magee. ARCHIVES. FEMINIST VISIONS: THE PRINCESS AND THE SQUAW: IMAGES OF AMERICAN INDIAN WOMEN IN CINEMA ROUGE, by Judith Logsdon. THE INDEXING OF WOMEN'S STUDIES JOURNALS: By Judith Hudson. RESEARCH EXCHANGE. FEMINIST PUBLISHING: A publishing handbook for the Caribbean area and a new lesbian and gay publisher in Canada. COMPUTER TALK. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Three directories - of nontraditional employment and training programs, of women's media, and of national women's organizations; bibliographies on feminist research methods, Victorian American women, contemporary women in politics, and women in agriculture; a biographical dictionary of women of the Revolutionary period; several resources on inclusive language; a guide to women's films; and a research tool on women, welfare, and higher education. (Reviewed by Phyllis Holman Weisbard) PERIODICAL NOTES: New periodicals on women working in film and video, women artists of African descent, British Black women, gender studies in central and eastern Europe, Charlotte Perkins Gilman, crones, Emily Dickinson, economic equality for women, Taiwanese women writers, indigenous North American and Pacific women, Australian lesbian feminist studies, lesbians, Arkansas women, Third World women in science, women's history, and women's studies in the UK. Special issues on lesbian art, the Clarence Thomas nomination, women's absence from the media, African American women artists, gender and technology, women in contemporary writing, women in the planning professions, feminist pedagogy, Eastern European Jewish women immigrants, and economic equity for women in the European Economic Community. Transitions: Feminist Voices halts publication temporarily; Herizons resumes after a long hiatus; and Wavelength looks for others to take over the publication. Ceased publication: INAVAW News. (Compiled by Linda Shult) ITEMS OF NOTE: Social Security information; vocational education resources for midlife and older women; a pamphlet on gender violence; several resources on violence against women and children; a directory of women in environmental work; two sources for hard-to-find books; a resource kit on working with immigrant women; health care resources; a periodicals guide; a Canadian women's directory; a bibliography of research on girls from K-12; a booklet on media outreach; a resource on women artists of color; a listing of film reviews; pamphlets on getting girls into science and math; and a new archival collection.(Compiled by Lisa Kaiser) BOOKS RECENTLY RECEIVED. SUPPLEMENT: INDEX TO FEMINIST COLLECTIONS, VOL.13.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews